Integrasi Pendidikan Karakter pada Program Tahfiz al-Quran: Studi Kasus Asrama Daarunnajah MAN 1 Magelang - Laila Sangadah; Asyharul Huda (Matan : Journal of Islam and Muslim Society, 2021)
This study aims to describe the curriculum design of tahfiz al-Quran in Darunnajah Dormitory MAN 1 Magelang. Primary data sources come from field observations and interviews. While secondary sources are obtained from books, journals, and references related to curriculum studies, character education and tahfiz al-Quran in general. The results showed that this program was structured by integrating several components including program objectives, basic competencies, strategies and methods of learning tahfiz al-Quran and using character values to teach memorizing the Quran. The design of the education-based tahfiz al-Quran curriculum is an attempt to internalize character values into students. These values include religious, diligent, honest, disciplined, independent, conscientious and responsible.